Importance of an individual's evaluation of functional status for health-related quality of life in patients with multiple sclerosis. Issue 3 (July 2015) - Gavelova, Miriam; Nagyova, Iveta; Rosenberger, Jaroslav; Krokavcova, Martina; Gdovinova, Zuzana; Groothoff, Johan W.; van Dijk, Jitse P.
Abstract: Background: Quantifying the clinical impact of multiple sclerosis (MS) is one of the most important determinants for optimizing individual patient care. Useful clinical measures for MS can be evaluated from different perspectives. Objective/Hypothesis: This cross-sectional study compared physical disability and functional status as assessed by a neurologist and by a patient and explored how they are associated with the health-related quality of life (HRQoL). Methods: We collected data from 223 patients. One neurologist scored functional disability using the Kurtzke's Expanded Disability Status Scale (EDSS) and patients evaluated their functional status using the Incapacity Status Scale (ISS). HRQoL was assessed using the Physical and Mental Component Summary (PCS, MCS) of the Short Form-36 Health Survey (SF-36). Multiple linear regressions were applied to analyze the data. Results: Total EDSS and ISS scores correlated significantly ( r = .67; p ≤ .001). Regression analyses showed that EDSS was significantly related to PCS, but not to MCS. After adding ISS into the analysis the association between EDSS and PCS became non-significant. ISS contributed significantly to the explained variance in both models. The final model explained 49% of the total variance for PCS and 15% for MCS. Conclusions: Functional disability as measured by a neurologist (EDSS) is associated with PCS, but not with MCS, whereas functional disability as measured by patients (ISS) is significantly associated with both HRQoL dimensions. Neurologists should target their attention more on patients' evaluations of their functional status in order to detect the most bothersome problems that are affecting a patient's quality of life.